AKTIVITAS ANTIBAKTERI EKSTRAK AKAR JERUK NIPIS (Citrus aurantifolia)TERHADAP BAKTERI Staphylococcus aureus DAN Escherichia coli DENGAN METODE DILUSI - Uswatun Liza Najiya; Uswatun Liza Najiya (Jurnal Kajian Ilmiah Kesehatan dan Teknologi, 2022)
ABSTRACT Background: Empirically, lime is widely used by the people of Indonesia both as a cooking spice, cough medicine, shed phlegm, influenza, antibacterial treatment of acne, and as an ulcer medicine. Objective: To determine the ability of lime (Citrus aurantifolia)root extract as an antibacterial against Staphylococcus aureus and Escherichia coli bacteria using the dilution method. Methods: Experimental research, using the maceration method with 96% ethanol solvent soaked 3x 24 hours, then thickened with a rotary evaporator, then antibacterial testing with S. aureus bacteria was carried out by the dilution method.Results: Simplicia lime root as much as 200 grams using 96% ethanol obtained a thick extract of 3.5 grams. The of secondary metabolites contain positive alkaloids, flavonoids, saponin and tannins. of the minimum inhibitory concentration (MIC) of Staphylococcus aureus bacteria with Escherichia coli were present at a concentration of 50% while the Minimum Killing Concentration of Staphylococcus aureus bacteria with Escherichia coli not found. Conclusion: The ethanolic extract of lime root (Citrus aurantifolia)has the ability as an antibacterial against Staphylococcus aureus bacteria with a MIC value of 50% concentration.contains positive secondary metabolite compounds,namely alkaloids, flavonoids,sapoons and tannins. The ethanolic extract of lime root (Citrus aurantifolia)did not have a Minimum Kill Concentration (KBM) value on Staphylococcus aureus and Escherichia coli. Keywords: (Citrus aurantifolia), E-coli, S.aureus, Dilution.